Mediation as an Instrument for Sustainable Business Dispute Resolution Based on the Principles of Corporate Sustainable Development - Ummi Maskanah; Al Fadillah Walduda’ini (Vifada Assumption Journal of Law, 2026)
Purpose: Business complexity increases disputes, while litigation is costly, time-consuming, adversarial, and risks damaging long-term relationships. This study analyses mediation’s legal position and mechanism in Indonesian business dispute resolution and its role in supporting Corporate Sustainable Development. Research Design and Methodology: This study uses descriptive-analytical legal research based primarily on a doctrinal or normative legal approach through statutory and conceptual approaches, supported only by limited empirical data. Primary legal materials are Law No. 30 of 1999 and Supreme Court Regulation No. 1 of 2016. Secondary materials include books, journal articles, and legal doctrines on mediation, alternative dispute resolution, business law, and corporate sustainability. Supporting empirical data were obtained from legal practitioners and mediators involved in business disputes and analysed qualitatively with the legal materials. Findings and Discussion: Mediation has a strong legal basis as a fair, flexible, confidential, and efficient mechanism. It supports Corporate Sustainable Development by preserving business relationships, protecting confidentiality, encouraging voluntary compliance, ensuring legal certainty, and strengthening responsible governance. Implications: This study positions mediation as a strategic legal instrument for sustainable business dispute management and recommends stronger mediation regulation, mediator competence, and mediation clauses in corporate governance policies.